Collision-induced Absorption Spectra of N2 and CH4 - Ryan M. Johnson; Peter F. Bernath; Brant Billinghurst; Jianbao Zhao (The Astrophysical Journal)
Collision-induced spectra are essential for radiative transfer modeling of Titan's atmosphere. We present experimental spectra of nitrogen–methane mixtures with an accompanying fit of N _2 -CH _4 collision-induced absorption in the 30–400 cm ^−1 region at about 130 K. We found a peak absorption of 2.30 × 10 ^−5 cm ^−1 amagat ^−2 at 75 cm ^−1 and a secondary peak of 1.35 × 10 ^−5 cm ^−1 amagat ^−2 at 206.5 cm ^−1 , which agrees with previous studies. Our work does not support the suggestion that N _2 -CH _4 CIA in the far-infrared should be increased by about 50%, as suggested by spectroscopic modeling of Titan using data from A. Borysow & C. Tang.